2022
DOI: 10.24187/ecostat.2022.534.2076
|View full text |Cite
|
Sign up to set email alerts
|

Household Inflation Expectations in France: Lessons from a New Survey and the COVID-19 Crisis

Abstract: Anticipations d'inflation par les ménages Crise sanitaire et situation financière des ménages Difficultés de recrutement des entreprises Critères de sélection des candidats dans les processus de recrutement Programme de développement rural et attractivité des territoires Covid-19 et baisse de la pollution de l'air : effets de long terme sur la mortalité Household Inflation Expectations Health Crisis and Household Financial Situation Recruitment Difficulties of Companies Selection Criteria of Candidates in Recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 107 publications
0
4
0
Order By: Relevance
“…[39][40][41] Reopening all businesses and getting back to a pre-pandemic economy helps to balance demand and supply, where imbalances are likely to increase inflation. [6][7][8]31 This study has some limitations. For example, a significant change in the consumption baskets of households during the pandemic may disrupt the supply and demand balance in the short and medium terms.…”
Section: Discussion and Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…[39][40][41] Reopening all businesses and getting back to a pre-pandemic economy helps to balance demand and supply, where imbalances are likely to increase inflation. [6][7][8]31 This study has some limitations. For example, a significant change in the consumption baskets of households during the pandemic may disrupt the supply and demand balance in the short and medium terms.…”
Section: Discussion and Limitationsmentioning
confidence: 96%
“…Bobeica and Hartwig 31 asserted that, in early 2021, the primary cause of high inflation was the increase in supply side and commodity prices. Moreover, Armantier et al, 6 Detmers et al, 7 and Gautier et al 8 suggested that both supply and demand shocks due to COVID-19 and the lockdown could be the reason for high inflation.…”
Section: Inflation-vaccine Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of perceptions about the development of past inflation on inflation expectations has attracted little attention in the literature. Only a handful of papers document a positive correlation between household's perceived and expected (twelve months ahead) inflation (Gautier and Montornès (2022) for France, D'Acunto 1 Inflation expectations are nowadays central for the analysis of monetary policy in macroeconomic models (Galí (2008)). On the policy relevance of inflation expectations, the current ECB-president Christine Lagarde, stated in 2020 that "for the actual process of setting wages and prices, it is the expectations of the public that matter most."…”
mentioning
confidence: 99%